PELANGGARAN MAKSIM KESANTUNAN BERBAHASA PADA KOLOM KOMENTAR TIKTOK TVONE NEWS TENTANG PEMBATASAN AKUN ANAK DI BAWAH 16 TAHUN - Wenny Nur Hamidah; Charisya Eka Anindya Shaputri Shaputri; Tika Yunia Saputri; Diah Lailatul Nikmah; Nur Lailiyah (Jurnal PENEROKA, 2026)
This study aims to analyze the forms and impacts of violations of politeness maxims based on Leech's Principle of Politeness theory in the comments section of the TikTok account @tvonenews regarding the social media account accounting policy for children under 16 years of age. The study used a non-geographic descriptive qualitative approach. The research data consisted of netizens' comments collected through listening, note-taking, and documentation techniques, then explained based on Leech's six politeness maxims. The results showed 29 violations spread across six types of maxims. The most violations occurred in the Humility Maxim, the Approval Maxim, and the Sympathy Maxim, with six data each, which indicated a tendency for netizens to convey criticism arrogantly, reject opinions confrontationally, and ignore empathy in responding to public policies. In contrast, only one violation of the Generosity Maxim was found because the communication context in the TikTok comment section rarely requires self-sacrifice. These findings indicate that violations of politeness principles have the potential to reduce the quality of public communication, increase trust in government policies, and strengthen opinion polarization in the digital space.